Exercise-Induced Fatigue Impairs Bidirectional Corticostriatal Synaptic Plasticity - Ma, Jing; Chen, Huimin; Liu, Xiaoli; Zhang, Lingtao; Qiao, Decai (Frontiers in Cellular Neuroscience, 2018)
Exercise-induced fatigue (EF) is a ubiquitous phenomenon in sports competition and training. It can impair athletes’ motor skill execution and cognition. Corticostriatal synaptic plasticity is considered to be the cellular mechanism of movement control and motor learning. However, the effect of exercise-induced fatigue on corticostriatal synaptic plasticity remains elusive. In the present study, using field excitatory postsynaptic potential recording, we found that the corticostriatal long-term potentiation (LTP) and long-term depression (LTD) were both impaired in exercise-induced fatigue mice. To further investigate the cellular mechanisms underlying the impaired synaptic plasticity in corticostriatal pathway, whole-cell patch clamp recordings were carried out on striatal medium spiny neurons (MSNs). MSNs in exercise-induced fatigue mice exhibited increased spontaneous excitatory postsynaptic current (sEPSC) frequency and decreased paired-pulse ratio (PPR), while with normal basic electrophysiological properties and normal sEPSC amplitude. Furthermore, the NMDA/AMPA ratio of MSNs was reduced in exercise-induced fatigue mice. These results suggest that the enhanced presynaptic glutamate (Glu) release and downregulated postsynaptic NMDA receptor function contribute to the impaired corticostriatal plasticity in exercise-induced fatigue mice. Taken together, our findings for the first time show that the bidirectional corticostriatal synaptic plasticity is impaired after exercise-induced fatigue, and suggest that the aberrant corticostriatal synaptic plasticity may be involved in the production and/or maintenance of exercise-induced fatigue.